2019
DOI: 10.1557/jmr.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical single-step obtention and characterization of a biomimetic TiO2-HA NTs covered by chitosan

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Electrochemical techniques offer an undeniable advantage over other techniques for synthesizing metallic HSS, such as a short processing time, and in many cases, biomimetic materials are obtained (Ren et al, 2006;Jiang et al, 2017;Liu et al, 2017;Galvão et al, 2019;Martínez-Cartagena et al, 2021). There are many examples of hard templates for the electrodeposition of threedimensionally ordered metals.…”
Section: Synthesis Of Hss Using Electrodepositionmentioning
confidence: 99%
“…Electrochemical techniques offer an undeniable advantage over other techniques for synthesizing metallic HSS, such as a short processing time, and in many cases, biomimetic materials are obtained (Ren et al, 2006;Jiang et al, 2017;Liu et al, 2017;Galvão et al, 2019;Martínez-Cartagena et al, 2021). There are many examples of hard templates for the electrodeposition of threedimensionally ordered metals.…”
Section: Synthesis Of Hss Using Electrodepositionmentioning
confidence: 99%
“…A. Pawlik et al also obtained a Ch-HAp coating on a Ti substrate using the electrophoretic deposition method and found that the deposition time and voltage affect the morphology of the coating [19]. Tubular structures based on Ti and Ch obtained by the electrochemical single-step process indicated their high potential in application as dental implants [20]. HAp/Ch-based coatings on Ti substrates have also been shown to be suitable for the immobilization of antibiotics and their local release into the biological environment [21].…”
Section: Introductionmentioning
confidence: 99%